Atom probe tomography study of an Fe25Ni25Co25Ti15Al10 high-entropy alloy fabricated by powder metallurgy. (15th October 2019) - Fu, Zhiqiang; Hoffman, Andrew; MacDonald, Benjamin E.; Jiang, Zhenfei; Chen, Weiping; Arivu, Maalavan; Wen, Haiming; Lavernia, Enrique J.
Abstract: In this study, transmission electron microscopy (TEM) and atom probe tomography (APT) were utilized to investigate the microstructure and phases in an Fe25 Ni25 Co25 Ti15 Al10 high-entropy alloy (HEA) prepared by mechanical alloying (MA) and spark plasma sintering (SPS). The bulk Fe25 Ni25 Co25 Ti15 Al10 HEA was characterized by a high tensile strength of 2.52 GPa and contained a minor bcc phase (∼17.7 vol%), together with a primary fcc phase (∼82.3 vol%) containing hierarchical nanoprecipitates. The bcc phase was a B2-type NiAl phase that contained substantial amounts of Co, Ti and Fe; it also exhibited Fe and Co rich nanoprecipitates with an average diameter of 1.11 ± 0.33 nm. The fcc phase consisted of a γ Fe-(Co, Ni)-based solid-solution matrix (A1), and coherent primary γ' (Ni, Co)3 -(Ti, Al)-based intermetallic precipitates (L12 ). A1 structured secondary γ* precipitates were found coherently embedded in the L12 -γ′ precipitates. We propose that the formation of the secondary γ* precipitates was largely driven by the unique chemical composition of the γ' precipitates which accommodate substantial amounts of Fe, Al and Ti, coupled with the nonequilibrium processing route used in our studies. Surprisingly, a novel type of Al–Ti–O oxide was identified via APT. A Ti(C, N) compound containing ∼9.19 at.% N and ∼12.27 at.% Ni was also detected by APT, rather than a simple TiC. Our analysis suggests that the Al–Ti–O oxide likely formed during MA, whereas the Ti(C, N) phase formed during sintering. In addition, a CALPHAD (Calculation of Phase Diagrams) approach was utilized to assist in understanding the underlying phase formation mechanisms. The notable high strength of 2.52 GPa in the Fe25 Ni25 Co25 Ti15 Al10 HEA support the hypothesis that phase formation mechanisms play an important role in the mechanical performance of HEAs fabricated by powder metallurgy. Graphical abstract: Image 1